Henri Rousseau - Venezia, Mike. (New York Children's Press, 2002)
An introduction to the life and work of the nineteenth-century French artist Henri Rousseau.
1 - 6
Keywords: Rousseau, Henri Julien Felix, 1844-1910.; Artists; Getting to know the world's greatest artists